2008
DOI: 10.1103/physrevlett.100.174102
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty-Limited Turnstile Transport in Deformed Microcavities

Abstract: We present both experimental and theoretical evidences for uncertainty-limited turnstile transport in deformed microcavities. As the degree of cavity deformation was increased, a secondary peak gradually emerged in the far-field emission patterns to form a double-peak structure. Our observation can be explained in terms of the interplay between turnstile transport and its suppression by the quantum mechanical uncertainty principle.PACS numbers: 05.45. Mt, 42.55.Sa, In the studies of quantum counterparts of cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Accordingly, deformed microcavities are realized in such a ultrasmall regime where the vacuum wavelength λ is of the order of the length scale of the cavity size R, i.e., R/λ ∼ 1 [8,9]. In this regime, high-Q WGMs still exist, but the emission from them is not as directional as from larger cavities, and the ray dynamical prediction of emission directionality is not valid anymore, because the resolutions of the modes are not enough to follow the fine structures in chaotic phase space [17,18]. So far, only the possibility of accidental coupling with low-Q modes is known to lead to directional emission [9].…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…Accordingly, deformed microcavities are realized in such a ultrasmall regime where the vacuum wavelength λ is of the order of the length scale of the cavity size R, i.e., R/λ ∼ 1 [8,9]. In this regime, high-Q WGMs still exist, but the emission from them is not as directional as from larger cavities, and the ray dynamical prediction of emission directionality is not valid anymore, because the resolutions of the modes are not enough to follow the fine structures in chaotic phase space [17,18]. So far, only the possibility of accidental coupling with low-Q modes is known to lead to directional emission [9].…”
mentioning
confidence: 96%
“…The deformed microcavities have been experimentally realized with several different cross-sectional shapes and various materials [6-10]. Also, they become important models in the field of quantum chaos [11,12] for the study of ray-wave correspondence in open systems [13][14][15][16][17].Nonetheless, it is not easy to understand and predict the spectrum and emission directionality because the internal ray dynamics is chaotic due to the broken rotational symmetry. Therefore, many studies have concentrated on the properties of the spectrum and the role of the chaotic dynamics to generate directional light emission from high-Q WGMs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the necessary condition of a continuous and single-line symmetric boundary shape, we can well control the directional emission from an ARC by setting boundary shape to adjust the stable islands and fixed points of unstable orbits in phase space. Actually, to some extent, the design of the dielectric ARC for directional emission is the control of chaotic transport in phase space [42]. Thanks to the ray-wave correspondence, the cavity for high-Q and unidirectional emission can be obtained by simple ray simulations.…”
Section: Discussionmentioning
confidence: 99%
“…25 It has been revealed that larger deformation breaks more KAM tori, enables more excitation light localized in the cavity, and leads to a higher probability of coupling into regular high-Q modes. 26 In addition, larger deformation has more potential for better unidirectionality, since controlling the chaotic behavior of rays in the cavity by unstable manifolds is fairly promising.…”
mentioning
confidence: 99%